2020
DOI: 10.1186/s12935-020-01255-2
|View full text |Cite
|
Sign up to set email alerts
|

A glycolysis-based 4-mRNA signature correlates with the prognosis and cell cycle process in patients with bladder cancer

Abstract: Background: Bladder cancer is one of the most prevalent malignancies worldwide. However, traditional indicators have limited predictive effects on the clinical outcomes of bladder cancer. The aim of this study was to develop and validate a glycolysis-related gene signature for predicting the prognosis of patients with bladder cancer that have limited therapeutic options. Methods: mRNA expression profiling was obtained from patients with bladder cancer from The Cancer Genome Atlas (TCGA) database. Gene set enri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…The nomogram can be used to diagnose or predict the onset or progression of a disease [ 13 ]. We established a nomogram according to the risk score and other clinicopathological parameters including age, gender, AJCC stage, T stage, and N stage ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…The nomogram can be used to diagnose or predict the onset or progression of a disease [ 13 ]. We established a nomogram according to the risk score and other clinicopathological parameters including age, gender, AJCC stage, T stage, and N stage ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…However, the predictive ability of single-gene biomarkers is limited in RCC prognosis analysis and multiple-genes signature maybe a better strategy [ 16 ]. So far, only four studies have established the glycolytic risk signature in lung adenocarcinoma [ 17 ], endometrial cancer [ 16 ], hepatocellular carcinoma [ 18 ] and bladder cancer [ 19 ]. Therefore, to explore the potential roles of glycolytic metabolism and glycolysis-related genes in RCC, a series of bioinformatic analyses were performed through TCGA database (609 samples).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have come to consistent conclusions. Using a glycolysis-based 4-mRNA signature, they found that high-risk group had higher mortality and poorer OS than low-risk group in bladder cancer [ 10 ]. It was generally held that glycolysis was related to poor prognosis in cancers, and the reliability of glycolysis score was demonstrated in another way.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, another enzyme, PKM2, plays an essential role in cell proliferation and cell cycle. The down-regulation of PKM2 suppressed proliferation of bladder cancer cells, with a decreased proportion of cells in the DNA synthesis phase [ 10 ]. Glycolysis plays a critical role in bladder cancer.…”
Section: Introductionmentioning
confidence: 99%